The Essay «Tobčilan ǰokiyaүsan šasin-u ǰiruqai orusiba» («A Brief Chronology of the Doctrine») of G.-Zh. Dylgyrov - Marina V. Ayusheeva (Монголоведение)
Introduction. The genre and thematic classification of religious writings in the Old Mongolian language largely repeats those in Tibetan literature. Among the Tibetan historical literature, researchers distinguish the genre of religious chronology (tib. bstan rtsis). They are both short and extensive works on the history of religion. The dates, names of figures, names of monasteries and writings contained in them are a valuable source on the history of Buddhism in India, Tibet and Mongolia. Among the Mongolian authors, one should name Sumba-hambo Ishbalzhir (1704–1788), the Ordos pandit Luvsanlhundeb (18th century), the Chahar Luvsantsultim (1740–1810), Lamyn-gegeen Luvsandanzanzhantsan (1639–1704), Galsan-Zhinba Dylgyrov (1816–1872) etc. Materials and methods. The article examines the printed text of G.-Zh. Dylgyrov named as “Briefly compiled chronology of the doctrine” and its handwritten copies stored at the Center for Oriental Manuscripts and Xylographs of the Institute for Mongolian, Buddhist and Tibetan Studies of the Siberian Branch of RAS. This xylograph was printed in 1866 in the printing house of the Tsugolsky Datsan. Results. The biography and written heritage of Buryat lama is briefly overviewed. A source-based description of text is given, significant dates in the history of Buddhism in India, Tibet and Mongolia are considered. Three systems of dating events are identified. Conclusions. The considered lists allow to conclude that G.-Zh. Dylgyrov’s work “Briefly compiled chronology of the doctrine” was widely distributed and in demand, and once again handwritten copies of it emphasize the traditions of Buryat written culture. Writings of this type were important for dating events and describing Buddhist history. The selectivity of the dates and events cited should be noted, which emphasizes the importance of these events for the author's worldview and his perception of history.